Congenital Disorders of Deficiency in Glycosaminoglycan Biosynthesis - Mizumoto, Shuji; Yamada, Shuhei (Frontiers in Genetics, 2021)
Glycosaminoglycans (GAGs) including chondroitin sulfate, dermatan sulfate, and heparan sulfate are covalently attached to specific core proteins to form proteoglycans, which are distributed at the cell surface as well as in the extracellular matrix. Proteoglycans and GAGs have been demonstrated to exhibit a variety of physiological functions such as construction of the extracellular matrix, tissue development, and cell signaling through interactions with extracellular matrix components, morphogens, cytokines, and growth factors. Not only connective tissue disorders including skeletal dysplasia, chondrodysplasia, multiple exostoses, and Ehlers-Danlos syndrome, but also heart and kidney defects, immune deficiencies, and neurological abnormalities have been shown to be caused by defects in GAGs as well as core proteins of PGs. These findings indicate that GAGs and PGs are essential for human development in major organs. The glycobiological aspects of congenital disorders caused by defects in GAG-biosynthetic enzymes including specific glysocyltransferases, epimerases, and sulfotransferases, in addition to core proteins of PGs will be comprehensively discussed based on the literature to date.